Liquid-Phase Synthesis of N-Functionalized Azanucleoside-Incorporated Oligonucleotides and Development of Anodic C(sp3)–H Acetoxylation Reaction for Direct Preparation of Azaribose - Okamoto, Kazuhiro; Shida, Naoki; Tsutsui, Mizuki; Chiba, Kazuhiro (Synlett, 2019)
We report the synthesis of pyrene-conjugated azanucleoside-incorporated oligodeoxynucleotides (aza-ODNs). Combination of liquid-phase synthesis by alkyl-chain-soluble-support (ACSS) and electrochemical C–H activation realized efficient access to aza-ODNs without requiring an excess amount of reagent or solvent. The fluorescent properties of pyrene-conjugated aza-ODNs were also investigated. The resulting fluorescence spectrum indicated that the modification of the position of the nitrogen atom was suitable for the preparation of artificial functionalized oligonucleotides. A synthetic route to azaribose, as a precursor of aza-ODNs, was also reinvestigated to realize more efficient production. Electrochemical N-α-acetoxylation in 0.1 M lithium perchlorate/nitromethane/50 mM AcOH medium was found to be a suitable medium for this route. These results represent a new efficient synthetic route to aza-ODNs.
Keywords: electrochemistry; C–H activation; nucleoside; nucleoside analogue; nucleic acid; acetoxylation Lewis acid